Development of Employee Payroll System using Rational Unified Process (RUP) on Odoo Platform - Fauzi Imaduddin Adhim; Raisya Fiany Martin; Slamet Budiprayitno; Lucky Putri Rahayu (Universitas Nahdlatul Ulama Surabaya, 2022)
Payroll process mostly done manually in Indonesian companies. Manual process takes longer time than automated process. In this research, an employee payroll system was developed on the Odoo platform by implementing the Rational Unified Process (RUP) method. There are four phases in this method, the inception phase includes business process modeling activities both ongoing business processes (as-is) and proposed business processes (to-be). Then from the business process needs analysis is carried out. The elaboration phase includes system design activities using use case diagrams, activity diagrams, configuration, use case scenarios, and salary rules. The construction phase includes implementation activities based on the system design in the previous phase. The results of the implementation will then be evaluated at the testing stage. In the final phase, namely the transition, the deployment or installation process is carried out to the user. The results obtained after testing the system by comparing salary calculations on Microsoft Excel and Odoo show that the total salaries of employees received are similar. The time needed to calculate an employee in Microsoft Excel is 15 minutes, while in Odoo the time needed is 6 minutes faster. In the User Acceptance Testing (UAT) test, the respondents involved were a limited circle of various departments at a sample company totaled 11 people by giving 12 statements from 3 UAT test criteria and obtained a final score of 86.97%. From the final score, the respondents accepted the developed system well.